Nursing Preparedness for Disaster Management in Bima, West Nusa Tenggara Province: An Assessment of Readiness Among Nurses - Darmawansah, Darmawansah; Seniwati, Tuti; Sabriyati, Wa Ode Nur Isnah (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Background: Indonesia has a high potential for disaster due to its geological and hydrometeorological location; as a result, community and government preparedness is needed, in this case, nurses at the community health centers. Bima City is one of Indonesia's cities with a high risk of floods and earthquakes. Objectives: This study aims to identify the current level of preparedness contain knowledge, skills, and disaster management of nurses in the city of Bima. Method: Quantitative non-experimental research method with a descriptive cross-sectional approach. Data collected by using an online research platform consist of Preparedness Evaluation Tools (DPET) questionnaire. Inclusion criteria included all nurses employed in health centers within Bima City with the minimum educational requirement of a Diploma Three in Nursing and expressing willingness to participate as respondents. Results: of the 97 respondents, there are 62.9% of nurses included in the category of being moderate prepared in dealing with disasters. Based on preparedness domain namely the level of knowledg, skill and disaster management, each are in the moderate prepared category with percentage of 67 %, 52,6%, 61,9 % respectively. Conclusion: the level of preparedness includes knowledge, skills and disaster management of nurses in Bima identified in the moderate prepared category. Suggestion: Nurses should read more literature about disasters and actively seek and attend disaster seminars and training